Swimming performance in elite triathletes: Comparison between open water and pool conditions - López-Belmonte, Ó.; Ruiz-Navarro, J. J.; Gay, A.; Cuenca-Fernández, F.; Arellano, R.; Cejuela, R. (Scandinavian Journal of Medicine & Science in Sports, 2024)
This study aimed to compare performance, kinematic, and physiological variables between open water and pool swimming conditions in elite triathletes and to examine the associations between conditions on these variables. Fourteen elite triathletes (10 males and 4 females [23.4 ± 3.8 years]) performed two 1500-m swimming tests in open water and in a 25-m pool. Swimming speed, stroke rate (SR), length (SL) and index (SI), heart rate (HR), blood lactate concentrations [La-], and end-exercise oxygen uptake (EEVO2) were assessed in both conditions. Lower SL and SI and higher SR were obtained in open water compared with pool swimming (p < 0.05). Moreover, kinematic variables changed as a function of distance in both conditions (p < 0.05). No differences were found in the main physiological variables (HR, [La-], and EEVO2) between conditions. Respiratory exchange ratio presented lower values in open water than in pool conditions (p < 0.05), while time constant was higher in open water (p = 0.032). The fastest triathletes in open water obtained the best performance in the pool (r = 0.958; p < 0.001). All kinematic variables, HR and peak [La-] presented positive associations between conditions (r > 0.6; p < 0.05). Despite physiological invariance, triathletes and coaches should monitor specific open water training to adapt their swimming technique to the competitive environment.